Enhancing the photoactivity of TiO2 by codoping with silver and molybdenum: the effect of dopant concentration on the photoelectrochemical properties. (25th April 2017) - Khan, Matiullah; Yi, Zeng; Fawad, U; Muhammad, Wazir; Niaz, Abdul; Zaman, Muhammad Iqbal; Ullah, Asad
Abstract: The concentration and nature of foreign atoms in titanium dioxide (TiO2 ) play a vital role in stabilizing the system as well as generating its optimal photocatalytic properties. A new pair of dopants is introduced to simultaneously improve the visible light harvesting and increase the separation between photoexcited carriers. Silver–molybdenum-codoped TiO2 with different doping concentrations was synthesized using a single-pot hydrothermal method. The synthesized samples showed a pure anatase phase with good crystallinity. Codoping shifted the absorption range of TiO2 towards the visible regime, and agglomerated particles with nearly spherical morphology were found. The existence of doped elements in TiO2 was verified by x-ray photoelectron spectroscopy and peaks relating to silver and molybdenum were detected. Based on their binding energy value, the peaks were attributed to their respective charge state and doping configuration. Among the synthesized samples, the 4% Ag–Mo-codoped TiO2 sample demonstrated the best visible light photodegradation response, attributed to the optimal doping concentration.